Seasonal Shifts in Diazotrophs Players: Patterns Observed Over a Two-Year Time Series in the New Caledonian Lagoon (Western Tropical South Pacific Ocean) - Saulia, Emmrick; Benavides, Mar; Henke, Britt; Turk-Kubo, Kendra; Cooperguard, Haley; Grosso, Olivier; Desnues, Anne; Rodier, Martine; Dupouy, Cécile; Riemann, Lasse; Bonnet, Sophie (Frontiers in Marine Science, 2020)
Coastal and open ocean regions of the Western Tropical South Pacific ocean have been identified as a hotspot of N2 fixation. However, the environmental factors driving the temporal variability of abundance, composition, and activity of diazotrophs are still poorly understood, especially during the winter season. To address this, we quantified N2 fixation rates and the abundance of seven diazotroph phylotypes (UCYN-A1 symbiosis, UCYN-B, UCYN-C, Trichodesmium, Het-1, Het-2 and Het-3) on a monthly basis during two full years (2012 to 2014) at four stations along a coast to open ocean transect in the New Caledonian lagoon. The total nifH gene concentration (sum of all nifH gene copies) clearly decreased from the barrier reef to the shore. Apart from UCYN-B, which peaked at very high abundances (106-108nifH gene copies L-1) at two occasions at the coastal station, the UCYN-A1 symbiosis was the most abundant group at all stations, accounting for 79 % of the total nifH gene copy counts along the transect (average abundance 4.2 ± 10.3 x 104 nifH gene copies L-1). The next most abundant groups were in order Trichodesmium (accounting for 14% of the total nifH gene copies), Het-groups (6% of the total) and UCYN-C (1% of the total). Statistical analyses reveal that the UCYN-A1 symbiosis and Het groups were associated with cold (<25°C) waters, high NOx and PO43-, weak winds from the south (occasionally southwest), while Trichodesmium and UCYN-C were associated with warmer (>25°C) waters, low NOx and PO43- concentrations, strong and (mostly) easterly winds. Average N2 fixation rates over the survey were 6.5 ± 6.7 nmol N L-1 d-1 and did not differ significantly among seasons. The interannual variability was more pronounced with average integrated rates significantly higher the second year of the survey (162 ± 122 μmol N m-2 d-1) than the first year (66 ± 91 μmol N m-2 d-1), likely due to higher seawater temperature. This dataset suggests that seasonality is less pronounced than previously thought, and that relatively high N2 fixation rates are maintained in the New Caledonian lagoon all year long, despite seasonal changes in the diazotroph community composition.